THE CONSTITUTIONAL TRADITIONS COMMON TO THE MEMBER STATES IN EU-ROPEAN LAW, AS A TOOL FOR COMPARISON AMONG MS LEGAL ORDERS IN THE CONSTRUCTION OF EUROPEAN FUNDAMENTAL RIGHTSAS TRADIÇÕES CONSTITUCIONAIS COMUNS AOS ESTADOS-MEMBROS NO DIREITO EUROPEU COMO FERRAMENTA DE COMPARAÇÃO ENTRE OS ORDENAMENTOS JURÍDICOS PARA A CONSTRUÇÃO DOS DIREITOS FUNDAMENTAIS EUROPEUS - Mangiameli (University of Teramo – IT), Stelio (Caderno de Relações Internacionais, 2017)
The article aims to investigate the traditions that are common to the countries that form the European Union as an instrument for the construction of the fundamen-tal rights of the European Union.